The Perception of Taxpayers Toward Goods and Services Tax (GST) Implementation - Nordiana, Ramli (2012)
This study was conducted to explore the relationship between local sales taxpayers', i.e. manufacturers', behavioral intention to comply with Goods and Service Tax (GST) in Kedah and Perlis. The manufacturers' behavioral intention was studied using Theory of Planned Behavior, consisting of variables such as attitudes, subjective norms, and perceived behavioral control. This study also added another variable i.e. law and enforcement. A total of 103 manufacturers participated in this study.Data collected and analyzed by using a multiple regression technique. Results of the study showed that only subjective norms and laws and enforcement affect behavioral intention to comply with local sales tax, while attitudes and perceived behavioral control did not affect behavioral intentions of local sales tax results. Variables in the study could explain 22% variance in behavioral intention.